1988
DOI: 10.1111/j.1365-2958.1988.tb00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity of §‐endotoxin genes with different insecticidal specificities in Bacillus thuringiensis aizawai 7.29

Abstract: The hypothesis according to which multiple and different delta-endotoxin genes could determine the host-range specificity of the lepidopteran strains of Bacillus thuringiensis is being checked in the case of strains aizawai 7.29 (serotype 7) and entomocidus 601 (serotype 6). From these strains, several crystal protein genes, belonging to different structural types, have been isolated. One of the cloned genes that is not present in strain entomocidus 601 is duplicated in strain aizawai 7.29. This gene belongs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
4

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 40 publications
4
39
1
4
Order By: Relevance
“…Several reports show a high frequency of certain cry1 gene combinations, for example the linkage cry1C-cry1D (Bravo et al 1998, Ferrandis et al 1999. The cry1C-cry1D linkage may be explained by their common location on the same replicon (Sanchis et al 1988). However, in this study cry1D gene was found alone at a relatively high frequency (24 strains) and only 7 strains presented such linkage.…”
Section: Discussioncontrasting
confidence: 50%
“…Several reports show a high frequency of certain cry1 gene combinations, for example the linkage cry1C-cry1D (Bravo et al 1998, Ferrandis et al 1999. The cry1C-cry1D linkage may be explained by their common location on the same replicon (Sanchis et al 1988). However, in this study cry1D gene was found alone at a relatively high frequency (24 strains) and only 7 strains presented such linkage.…”
Section: Discussioncontrasting
confidence: 50%
“…The Cry1Ab protoxin was 131 kDa in size (Gohar, personal communication), and was obtained from a gene cloned from the aizawai 7.29 strain in the pHTA1 plasmid (Sanchis et al, 1988).…”
Section: Tested Syrupsmentioning
confidence: 99%
“…This strain was a derivative of the wild-type B. thuringiensis strain 407 isolated by Lereclus et al (1989) which displayed the cry1Ab gene described by Sanchis et al (1988) without producing any spores. Consequently any differences in susceptibility among strains could be attributed to the Cry1Ab toxin.…”
Section: Methodsmentioning
confidence: 99%